The structure of equilibria in trading networks with frictions - Jan Christoph Schlegel (Theoretical Economics, 2022)
Several structural results for the set of competitive equilibria in trading networks with frictions are established: The lattice theorem, the rural hospitals theorem, the existence of side-optimal equilibria, and a group-incentive-compatibility result hold with imperfectly transferable utility and in the presence of frictions. While our results are developed in a trading network model, they also imply analogous (and new) results for exchange economies with combinatorial demand and for two-sided matching markets with transfers.
Keywords: C78; D47; D52; L14; 330; Trading Networks; Full Substitutability; Imperfectly Transferable Utility; Competitive Equilibrium; Indivisible Goods; Frictions; Lattice; Rural Hospitals